The Influence of Question and Answer Methods on The Development of Critical Thinking in Early Children - Yolandha Asika Putri (Department of Early childhood Education, 2020)
The conclusion from eleven journals that discuss critical thinking, namely using various methods to achieve increased critical thinking in children. Of the various methods and methods used have their respective interests to attract attention to children to follow every step taken to improve critical thinking in children. Among them using puzzle games, role playing methods, scientific methods, experimental methods, introduction to the concept of hours, methods of play, of all the methods used, children can analyze, find out the cause and effect, find a way out of the problems they are doing in the activities or games that they do it by thinking critically or thinking broadly. It can be concluded that the nine journals that use the question and answer method can develop children's language, speaking skills, social emotional, learning motivation, and good communication. From all of the above, it allows children and teachers to establish good two-way communication, to optimize learning, also not forget to insert fun and interesting activities for children so that children feel happy and interested in activities as well as every communication that exists. With learning that is fun and interesting for children, the development of the children will increase optimally in the present and in the future. From all of the above, it allows children and teachers to establish good two-way communication, to optimize learning, also not forget to insert fun and interesting activities for children so that children feel happy and interested in activities as well as every communication that exists. With learning that is fun and interesting for children, the development of the children will increase optimally in the present and in the future. From all of the above, it allows children and teachers to establish good two-way communication, to optimize learning, also not forget to insert fun and interesting activities for children so that children feel happy and interested in activities as well as every communication that exists. With learning that is fun and interesting for children, the development of the children will increase optimally at present and in the future.